2017
DOI: 10.5014/ajot.2017.027219
|View full text |Cite
|
Sign up to set email alerts
|

Animal-Assisted Therapies and Dementia: A Systematic Mapping Review Using the Lived Environment Life Quality (LELQ) Model

Abstract: The findings offer proof of the concept that canine-assisted therapies are feasible and can elicit positive quality-of-life experiences in institutionalized people with dementia. Researchers and practitioners need to elucidate the theoretical foundations of AATs. The LELQ Model may serve as a guide for client-centered, occupation-focused, and ecologically valid approaches to animal-assisted occupational therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…6 A recent systematic mapping review found that animalassisted therapies in LTC facilities may help to enhance the QoL of older adults with Alzheimer's disease and other dementias, referred to simply as "dementia" in this article. 7 Although not without methodological weaknesses, the 10 studies included in this review offered evidence that therapies that incorporate dogs may help LTC residents with dementia occupy time in diverse ways, use their existing capacities in meaningful activities, and experience heightened emotional well-being. This article reports on a study of an equineassisted activities program (EAAP) that was guided by the same conceptual model that directed the mapping review, the Lived Environment Life Quality (LELQ) Model.…”
Section: Introductionmentioning
confidence: 99%
“…6 A recent systematic mapping review found that animalassisted therapies in LTC facilities may help to enhance the QoL of older adults with Alzheimer's disease and other dementias, referred to simply as "dementia" in this article. 7 Although not without methodological weaknesses, the 10 studies included in this review offered evidence that therapies that incorporate dogs may help LTC residents with dementia occupy time in diverse ways, use their existing capacities in meaningful activities, and experience heightened emotional well-being. This article reports on a study of an equineassisted activities program (EAAP) that was guided by the same conceptual model that directed the mapping review, the Lived Environment Life Quality (LELQ) Model.…”
Section: Introductionmentioning
confidence: 99%
“…The search procedure for the present study is consistent with the search procedure reported in previously developed papers [21, 30]. Using approximately 45 search criteria and beginning in 2015, a library scientist developed and executed four comprehensive searches in the following databases to assist in multiple projects regarding equine-assisted activities or therapies: CAB Abstracts (EBSCO), CINAHL (EBSCO), PsycINFO (EBSCO), PubMed (NCBI), Social Sciences Abstracts (EBSCO), Social Services Abstracts (ProQuest), Social Work Abstracts (EBSCO), SPORTDiscus (EBSCO), and Web of Science (Thomson Reuters).…”
Section: Methodsmentioning
confidence: 65%
“…In a mapping review, Wood, Hoesly, Rose, and McLure (2017) found 10 research articles discussing the use of canineassisted therapies for adults with dementia in institutionalized settings. These studies support the feasibility of using animalassisted therapy models in institutional settings and the positive effects such models can have on QOL.…”
Section: Knowledge Synthesismentioning
confidence: 99%